Spectral Shifts and Dissociation Dynamics of Acetone in the Presence of an External Electric Field - Liu, Xinyao; Majeed, M. Umar; Han, Boyuan; Khalil, Hassnain; Liu, Yuzhu (Journal of Environmental Science and Engineering Technology, 2025)
Acetone, a typical volatile organic compound (VOC), poses significant environmental and health risks due to its high reactivity and contribution to the photochemical smog formation. The effects of an external electric field (EEF) ranging from 0 to 30.854 V·nm-1 on the physical and chemical properties of acetone were investigated by density functional theory (DFT) using the B3LYP/6-311+g(2d,2p) basis set. The results demonstrate that the C=O bond in acetone elongates and the total moment increases as the EEF increases, enhancing molecular polarization. Although the total energy of acetone decreases with increasing EEF, the change is primarily due to the dipole-field interaction, and does not necessarily indicate improved thermodynamic stability. The infrared (IR), Raman, and UV-Vis spectra exhibit redshifts, indicating a reduction in excitation energy. Single-point energy scans confirm that the C=O bond weakens, with dissociation predicted at 52.785 V·nm-1.